Coronavirus disease-2019: Challenges, opportunities, and benefits in India - Riwanka Khlem; Sujatha R Kannappan; Papori Pathak Choudhury (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The human coronavirus was first identified in 1965, belongs to the same family of Viruses as SARS, MERS-Co. The current virus that affected worldwide came into existence in late 2019, recently found in Wuhan, China, and caused a global pandemic called coronavirus disease-2019 (COVID-19). This disease became a quick global pandemic due to the rapid transmission of the virus from one human to another. In the history of humankind, people were inside the four walls for more than a month. The COVID-19 pandemic has posed significant problems in a variety of fields. The current pandemic created many changes that are seen as challenges worldwide. However, it created opportunities and benefits for many, extend a helping hand towards the people in need, in the society, community, and the nation. This paper focuses on challenges, opportunities, and benefits during the (COVID-19) pandemic in India. MATERIALS AND METHODS: Online search engines like PubMed and Google Scholar were used to conduct the research. The review article's dates were not restricted in any way. A total of 48 articles were chosen. The data was tabulated based on the kind of study and the outcomes. There are just a few papers available that demonstrate the necessity for more study. RESULTS: COVID-19 caused unforeseen changes in the health care industry, unequal distribution of health care, and consequences on mental health, according to the review studies. Teleconsultation, Internet use, and E-learning have all become more accessible. A period of transitory economic collapse and an increase in the number of migrants left many despondent. Improvement in family bonding, use of a face mask, and hygiene measures to adapt to the current scenario. There was also an impact on water sources, waste management systems, and environmental resource conservation. CONCLUSION: Difficult conditions can provide both problems and opportunities and advantages to the people during a pandemic outbreak.